The ecological legacies of drought, fire, and insect disturbance in western North American forests - Assal, Timothy J., author; Sibold, Jason S., advisor; Bowen, Zachary H., committee member; Chong, Geneva W., committee member; Knight, Richard L., committee member; Morisette, Jeffrey T., committee member (Colorado State University. Libraries, 2015)
Temperate forest ecosystems are subject to various disturbances including insect agents, drought and fire, which can have profound effects on the structure of the ecosystem for many years after the event. Impacts of disturbance can vary widely, therefore an understanding of the legacies of an event are critical in the interpretation of contemporary forest patterns and those of the near future. The primary objective of this dissertation was to investigate the ecological legacies of drought, beetle outbreak and ensuing wildfire in two different ecosystems. A secondary objective of my research, data development, was motivated by a lack of available data which precluded ecological investigation of each disturbance. I studied the effects of drought on deciduous and coniferous forest along a forest-shrubland ecotone in the southern portion of the Wyoming Basin Ecoregion. The results show that forests in the region have experienced high levels of cumulative drought related mortality over the last decade. Negative trends were not consistent across forest type or distributed randomly across the study area. The patterns of long-term trends highlight areas of forest that are resistant, persistent or vulnerable to severe drought. In the second thread of my dissertation, I used multiple lines of evidence to retrospectively characterize a landscape scale mountain pine beetle disturbance from the 1970s in Glacier National Park. The lack of spatially explicit data on this disturbance was a major data gap since wildfire had removed some of the evidence from the landscape. I used this information to assess the influence of beetle severity on the burn severity of subsequent wildfires in the decades after the outbreak. Although many factors contribute to burn severity, my results indicate that beetle severity can positively influence burn severity of wildfire. This is likely due to the change in forest structure in the decades after the outbreak and not as a direct result of tree mortality from the outbreak. The long-term perspective of this study suggests that ecological legacies of high severity disturbance may continue to influence subsequent disturbance for many years after the initial event. This work also provides insight on future disturbance interactions associated with the recent mountain pine beetle outbreak that has impacted tens of millions of hectares in western North America over the last two decades.
Keywords: drought; forest disturbance; insect outbreak; remote sensing; tree mortality; wildfire